2020
DOI: 10.1590/0034-7167-2019-0735
|View full text |Cite
|
Sign up to set email alerts
|

Hemovigilance and patient safety: analysis of immediate transfusion reactions in elderly

Abstract: Objective: To identify immediate transfusion reactions in elders hospitalized in a public hospital in the Federal District. Methods: This is an observational, retrospective, documental, and analytical research, with a quantitative analysis of 516 transfusions of packed red blood cells in elders hospitalized in the largest public hospital, who required blood components, from June to December 2017, through descriptive statistics. Results: The sample corresponded to 46.36% of the total number of transfusions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
1
1
5
Order By: Relevance
“…Underreporting was also found in a study conducted by Surekha K et al, Incidence in our study was found to be 1.17% which was different from a study conducted by Surekha K et al (0.3%), Bhattacharya et al (0.18%), and Praveen Kumar et al, (0.05%) [8,9,10]. A hemovigilance study conducted in Portuguese among elderly people shown a high rate of adverse transfusion reactions compared to the current study [11].…”
Section: Resultscontrasting
confidence: 84%
“…Underreporting was also found in a study conducted by Surekha K et al, Incidence in our study was found to be 1.17% which was different from a study conducted by Surekha K et al (0.3%), Bhattacharya et al (0.18%), and Praveen Kumar et al, (0.05%) [8,9,10]. A hemovigilance study conducted in Portuguese among elderly people shown a high rate of adverse transfusion reactions compared to the current study [11].…”
Section: Resultscontrasting
confidence: 84%
“…Portanto, fatores propensos as dificuldades em suprir hemocomponentes em emergências médicas, sobre tudo nas patologias clínicas correlacionadas á internações hospitalares por patologias do sangue e dos órgãos hematopoéticos e alguns transtornos imunitários são comumente evidenciados (Sobral et al, 2020).…”
Section: Introductionunclassified
“…5,9 Nurses having knowledge on hemovigilance subsequently increased their understanding of different types of the blood products, the ways to transfuse and maintain blood products, the way to transfer the products, different blood types and tests required for the blood transfusion process, the required facilities and equipment, and the reactions to blood and the blood products. 10 The nurse's knowledge in this field makes it possible to monitor the transfusion process and the management of the blood carefully and to record all the incidents and then use them for further evaluations while monitoring patients closely and continuously. 11,12 Controlling the orders, caring patients, obtaining their consent, and educating them about health issues are known as the most important tasks of nurses during the hemovigilance process; so, they should have knowledge on them.…”
Section: Introductionmentioning
confidence: 99%